Dinámica de comunidades vegetales en el valle semiárido de Zapotitlán, Puebla: un enfoque de metacomunidades y ecología de las invasiones - Jiménez, María de Jesús Monserrat (Universidad Autónoma Metropolitana, 2021)
The recognition of patchy and heterogeneous landscapes has been important in the ecology of communities, this has allowed to evaluate in a more realistic way their dynamics and structure in a hierarchy of interrelated spatial scales (local and regional) within a scheme of metacommunities, where species in local communities potentially interact through competition and dispersal. Besides, the dynamics of metacommunities is linked to invasion-colonization processes, which are influenced by the ability of individuals to establish themselves in patches different from the one they come from, and by the susceptibility (invasiveness) of a community to species that arrive from other regions or patches to establish themselves. Under this scheme, we evaluated the possible processes (biotic interactions, environmental filtering and dispersal) that could explain the spatial and temporal dynamics in two plant communities surveys (1980 to 2003) of a semi-arid metacommunity in the Zapotitlán Valley, Puebla. The studied metacommunity comprised 26 patches that encompassed three types of vegetation: (1) cardonal, characterized by the presence of the unbranched columnar cactus Cephalocereus column-trajani; (2) tetechera characterized by the dominance of the branched columnar cactus Cephalocereus tetetzo; and (3) thorn-scrub, characterized by the presence of thorny trees and shrubs, legumes, agaves and small cacti. The dispersal capacity of the species present in the metacommunity was evaluated from the morphometric and functional features of their dispersal structures (fruits and seeds). We generated a dispersibility index (i.e., dispersal ability) at the species and community levels, where we found a gradient in the dispersal capacity of species and communities. Trough one year (May 2011 through May 2012) we evaluated the dynamics of the rain and the seed bank to determine the entry of propagules to the different communities and their effect on the structure of the vegetation The permanence in the seed bank was explored through an experiment in which we buried seeds of six species (Echinocactus platyacanthus, Mammillaria carnea, Beaucarnea gracilis, Mariosousa acatlensis, Heterotheca inuloides and Hechtia tehuacana) with different dispersibility, which we unearthed at different times (after 1 day, and after 6, 12, 15 and 24 months) and we put them to germinate under laboratory conditions. The dynamics of the rain and seed bank varied between the dry and rainy seasons. We did not find a correspondence between the seed rain and the seed bank with the standing vegetation. Of the six buried species, only M. acatlensis does not seem to form a seed bank. The invasiveness of the communities was also evaluated with a field experiment at the microcosm level under the canopies of Prosopis laevigata. In 18 microcosms with different environmental conditions and species diversity, we placed seeds of the six selected species. We did not find significant differences in germination and establishment between the three vegetation types. Differences were found between species’ germination and establishment. Mariosousa acatlensis and Beaucarnea gracilis showed the highest germination percentage and the later showed the highest establishment value. The diversity of the species already established under the crown of the shrubs had a positive relationship with the germination and establishment of the introduced species. Finally, we evaluated changes in the composition and abundance of the species in local communities and their influence on the structure of the metacommunity and the possible variables that determine it. The structure of the metacommunity and its relationship with environmental (edaphic) and spatial variables (altitude, slope and geographic location) were analyzed through the elements of metacommunity structure and the importance of environmental filters from the variance partition analysis. For the 1980 survey, a clementsian n structure was determined, which remained unchanged after 23 years, although the relative importance of environmental filters with respect to spatial dispersion filters decreased from 1980 to 2003. The dynamics and structure of the metacommunity under study can be explained, at least partially, by the characteristics of the species (dispersibility, permanence in the seed bank and establishment) and of the local communities (invasibility) as environmental factors and biotic interactions. This suggests that the coexistence mechanism in the metacommunity would be through species selection, where the species would be selected according to their tolerances and requirements against the biotic and abiotic factors of each patch. Local communities and the meta-community must be continuously monitored to understand the long-term structuring of these systems. Keywords: clementsian structure, dispersal, environmental filters, invasibility, invasions, metacommunity dynamics.; El reconocimiento de paisajes en parches y heterogéneos ha sido importante en la ecología de comunidades, ya que ha permitido evaluar de manera más realista su dinámica y estructura en una jerarquía de escalas espaciales (local y regional) interrelacionadas dentro de un esquema de metacomunidades, donde las especies de las comunidades locales interactúan potencialmente mediante competencia y dispersión. A su vez, la dinámica de metacomunidades está ligada con los procesos de invasión-colonización, que son influenciados por la capacidad de los individuos de establecerse en parches diferentes al que provienen, y por la susceptibilidad (invasibilidad) de una comunidad a que las especies que llegan de otras regiones o parches logren establecerse. Bajo este esquema, evaluamos los posibles procesos (interacciones bióticas, filtrado ambiental y dispersión) que podrían explicar la dinámica espacial y temporal (1980 a 2003) de una metacomunidad semiárida del valle de Zapotitlán, Puebla. La metacomunidad de estudio comprendió 26 parches que abarcaron tres tipos de vegetación: (1) cardonal, caracterizado por la presencia del cactus columnar no ramificado Cephalocereus columna-trajani; (2) tetechera, donde domina el cactus columnar ramificado Cephalocereus tetetzo; y (3) matorral, que se caracteriza por la presencia árboles y arbustos espinosos, leguminosas, agaves y pequeños cactus. La capacidad de dispersión de las especies presentes en la metacomunidad se evaluó a partir de los rasgos morfométricos y funcionales de sus estructuras de dispersión (frutos y semillas) y generamos un índice de dispersabilidad (esto es, capacidad de dispersión) a nivel de especie y de comunidad, con el cual encontramos un gradiente en la capacidad de dispersión de las especies y de las comunidades. Durante un año (mayo de 2011 a mayo de 2012) 2 evaluamos las dinámicas de la lluvia y del banco de semillas para determinar la entrada de propágulos a las diferentes comunidades y su efecto en la estructura de la vegetación. La permanencia en el banco de semillas fue explorada mediante un experimento en el que enterramos semillas de seis especies (Echinocactus platyacanthus, Mammillaria carnea, Beaucarnea gracilis, Mariosousa acatlensis, Heterotheca inuloides y Hechtia tehuacana) con diferente dispersabilidad, que desenterramos a diferentes tiempos (1 día, 6, 12, 15 y 24 meses) y las pusimos a germinar en condiciones de laboratorio. La dinámica de la lluvia y banco de semillas varió entre la época de secas y de lluvias. No encontramos correspondencia entre la lluvia y el banco con la vegetación ya establecida. De las seis especies enterradas, M. acatlensis no forma banco de semillas. La invasibilidad de las comunidades también la evaluamos con un experimento de campo a nivel de microcosmos formados debajo de copas de Prosopis laevigata. En 18 microcosmos con diferentes condiciones ambientales y diversidad de especies, colocamos semillas de las seis especies seleccionadas. No encontramos diferencias significativas en la germinación y establecimiento entre los tres tipos de vegetación estudiados. Se encontraron diferencias entre especies en su porcentaje de germinación y establecimiento. Mariosousa acatlensis y B. gracilis registraron los mayores valores de germinación y la segunda especie el mayor valor de establecimiento porcento. La diversidad de las especies ya establecidas debajo de la copa de los arbustos tuvo una relación positiva con la germinación y establecimiento de las especies. Por último, evaluamos los cambios en la composición y abundancia de las especies en las comunidades locales y su influencia en la estructura de la metacomunidad y las posibles variables que la determinan. La estructura de la metacomunidad y su relación con variables ambientales (edáficas) y espaciales (altitud, pendiente y ubicación geográfica) se analizaron a través de los elementos de estructura de metacomunidades y la importancia de los filtros ambientales a partir de la partición de varianza. Para el muestreo de 1980 se determinó una estructura clementsiana, la cual se mantuvo sin cambios luego de 23 años, aunque la importancia relativa de los filtros ambientales con respecto a los filtros espaciales de dispersión disminuyó de 1980 a 2003. La dinámica y estructura de la metacomunidad de estudio puede ser explicada, al menos parcialmente, por las características de las especies (dispersabilidad, permanencia en el banco de semillas y establecimiento) y de las comunidades locales (invasibilidad) como factores ambientales e interacciones bióticas. Esto sugiere que el mecanismo de coexistencia en la metacomunidad sería a través de la selección de especies, donde las especies serían seleccionadas de acuerdo con sus tolerancias y requisitos frente a los factores bióticos y abióticos de cada parche. Las comunidades locales y la metacomunidad deben ser monitoreadas continuamente para comprender la estructuración a largo plazo de estos sistemas. Palabras clave: dinámica de metacomunidades, dispersión, estructura clementsiana, filtros ambientales, invasibilidad, invasiones.